Fast Disintegrating Combination Tablet of Taste Masked Levocetrizine Dihydrochloride and Montelukast Sodium: Formulation Design, Development, and Characterization. (30th March 2014) - Gupta, M. M.; Gupta, Niraj; Chauhan, Bhupendra S.; Pandey, Shweta
Abstract : The aim of this study was to prepare fast disintegrating combination tablet of taste masked Levocetrizine dihydrochloride and Montelukast sodium by using direct compression method. To prevent bitter taste and unacceptable odour of the Levocetrizine dihydrochloride drug, the drug was taste masked with ion exchange resins like Kyron-T-104 and Tulsion-412. Among the two resins, Kyron-T-104 was selected for further studies because of high drug loading capacity, low cost, and better drug release profile. An ion exchange resin complex was prepared by the batch technique and various parameters; namely, resin activation, drug: resin ratio, pH, temperature, and stirring time, and swelling time were optimized to successfully formulate the tasteless drug resin complex (DRC). The tablets were prepared using microcrystalline cellulose (MCC) PH 102 as diluent along with crospovidone (CP), croscarmellose sodium (CCM), and sodium starch glycolate (SSG) as a superdisintegrants. The tablets were evaluated for weight variation, hardness, friability, wetting time, water absorption ratio, disintegration time (DT), and dissolution study and it was concluded that the tablet formulation prepared with 2% SSG + CCS showed better disintegration time in comparison with other formulation and good drug release. The stability studies were carried out for the optimized batch for three months and it showed acceptable results.